Torsion of paraovarian cyst: An enigma - Latika; Dahiya, Pushpa (Asian Journal of Medical Sciences, 2024)
Paraovarian cysts are extremely rare and represent approximately 10% of adnexal masses. They are found commonly in women of reproductive age group and arise from the mesothelium. Paraovarian cyst is an entity which is rarely diagnosed preoperatively and often remains undiagnosed and missed out even by radiologists. Most often they remain asymptomatic but when large in size may present with complications such as torsion, hemorrhage, and infection. Isolated torsion of paraovarian cyst is extremely rare. Its diagnosis is often missed out leading to complications.